(untitled) (Materiali di Estetica. Terza serie, 2024)
The monographic section of this issue of Materiali di Estetica explores the role of negative emotions in art, inspired by theories from Aristotle to 18th- and 19th-century scholars. It delves into the "sublime," loneliness, pain, and fear as explored through various media, including painting, photography, music, and cinema, connecting historical reflections with contemporary research like neuroscience and cognitive science. The issue also honors poets Federica Schiaffino and Clara Janès, presents insights into Fulvio Papi’s work, and features discussions on art, philosophy, and politics, concluding with reviews and a call for papers on empathy in music.